CLINICAL AND LABORATORY FEATURES OF INTERSTITIAL NEPHRITIS IN CHILDREN WITH PURINE DYSMETABOLISM - Sidikova Maryam Amangeldiyevna (Web of Journals Publishing, 2024)
The purpose of the study. Explore the clinical and laboratory features of the flow of interstitial nephritis in children that developed on the background of hyperuricemia and hyperuricosuria. Materials and methods. Examined 84 patients with an established diagnosis of interstitial nephritis dysmetabolic genesis background urikozurii more uric acid 1mg to 1ml of urine. Metabolic status of the patients was evaluated by a special program, which included a genealogical analysis, screening tests and quantitative biochemical studies. As the main biochemical marker to determine the level uricemia (> 320mkmol / l) and urikozurii. Results. Comparative analysis has shown that the difficulties can be overcome diagnosis by careful comparison of medical history, clinical and laboratory data and timely diagnosis urikozuric genesis nephropathy. Found that when dismetabolic interstitial nephritis unlike glomerulonephritis in the disease onset is no extra renal symptoms, does not suffer from glomerular filtration, azoth-excretory renal function. The diagnosis is confirmed by the presence of the characteristic spectrum of extra renal disease in the pedigree, the presence of hyperuricemia (> 0,310mmol / l) and urikozurii (> 1.0 mg uric acid 1ml urine). The most informative of the disease is the debut at an early age, the absence of extra renal symptoms in the presence of isolated bladder syndrome.
Keywords: children, hyperuricemia, hyperuricosuria, interstitial nephritis.